-3(2u-x)-4(x+4u)=

Simple and best practice solution for -3(2u-x)-4(x+4u)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2u-x)-4(x+4u)= equation:


Simplifying
-3(2u + -1x) + -4(x + 4u) = 0
(2u * -3 + -1x * -3) + -4(x + 4u) = 0
(-6u + 3x) + -4(x + 4u) = 0

Reorder the terms:
-6u + 3x + -4(4u + x) = 0
-6u + 3x + (4u * -4 + x * -4) = 0
-6u + 3x + (-16u + -4x) = 0

Reorder the terms:
-6u + -16u + 3x + -4x = 0

Combine like terms: -6u + -16u = -22u
-22u + 3x + -4x = 0

Combine like terms: 3x + -4x = -1x
-22u + -1x = 0

Solving
-22u + -1x = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add 'x' to each side of the equation.
-22u + -1x + x = 0 + x

Combine like terms: -1x + x = 0
-22u + 0 = 0 + x
-22u = 0 + x
Remove the zero:
-22u = x

Divide each side by '-22'.
u = -0.04545454545x

Simplifying
u = -0.04545454545x

See similar equations:

| (x+3)(2x-5)=40 | | -12=(-7)-3.5s | | 2(3x-4)=5(x+7) | | 41=-7x+2(x+8) | | 19+2x=-37+6x | | 6x-21=5(x-3) | | 3/4/5 | | 1/5x=3-1/x | | 125-5=p | | 4(y-2)=9y+27 | | 1.2+2.6g=0.1 | | -11v-3=-24 | | 9w-21=3(w+1) | | -52-3v=8 | | -6x-4(-x-9)=58 | | -8=x/8 | | -50-5x=3x+30 | | 2a^2=8a^2b^2 | | 3x+38=-67+4x | | 25=10x+15 | | 23/4+x=7 | | x^2-5x+2=1-3x | | (x/2)-25=18 | | .7(.3x-.8)=-4.48 | | d^3+1=0 | | 2x^2+50x-20x=0 | | 3x+5(15)= | | 1369373+6472= | | 2y-4x=18 | | 66=3(2x-4) | | 10-8(x-6)=2-4x | | 3(16)-4y= |

Equations solver categories